2015
DOI: 10.1684/mst.2014.0420
|View full text |Cite
|
Sign up to set email alerts
|

Role of laparoscopy in the diagnosis of peritoneal tuberculosis in endemic areas

Abstract: rê t de la laparoscopie dans le diagnostic de la tuberculose pé ritoné ale en zones endé miques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…AFB smear, cultures and GeneXpert have a low sensitivity, <5%, 45–69% and 18% respectively [ 7 ]. Peritoneal biopsy by laparoscopy (for AFB smear, culture, molecular and pathology tests) may be required to establish the diagnosis [ 61 ]. The peritoneum has the appearance of millet seeds.…”
Section: Frequent Locations Of Eptmentioning
confidence: 99%
“…AFB smear, cultures and GeneXpert have a low sensitivity, <5%, 45–69% and 18% respectively [ 7 ]. Peritoneal biopsy by laparoscopy (for AFB smear, culture, molecular and pathology tests) may be required to establish the diagnosis [ 61 ]. The peritoneum has the appearance of millet seeds.…”
Section: Frequent Locations Of Eptmentioning
confidence: 99%
“…Our findings further highlight the reported low sensitivity rates of acid-fast bacilli and Ziehl-Neelsen staining in detection of Tubercle bacilli in ascitic fluid [24][25][26], and the poor sensitivity and specificity of Gene expert in detection of abdominal TB from ascitic fluid samples [27]. The diagnosis of peritoneal tuberculosis in our case, like other related cases [17,18] was made through histological examination of intraoperative collected tissue samples, further stressing the need of pathological examination of samples as the gold standard for definitive diagnosis of peritoneal tuberculosis [28,29] Abdominal tuberculosis is generally responsive to medical treatment. Isoniazid, rifampin, pyrazinamide, ethambutol, and streptomycin are the five common first line medication for treatment of Tuberculosis with treatment duration consisting of a four-drug regimen administered for 2 months then continuation of treatment with rifampin and isoniazid for 4 or more months [30].…”
Section: Discussionmentioning
confidence: 68%
“…A recent study of 43 cases of PTB showed that initial screen for mycobacterium and final cultures in the ascitic fluid were negative in all the patients. 1 However, surgically obtained peritoneal biopsies were positive in all 43 patients for mycobacterium.…”
Section: Case Reportmentioning
confidence: 91%